2009
DOI: 10.1111/j.1600-0625.2008.00771.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C isoenzymes differentially regulate the differentiation‐dependent expression of adhesion molecules in human epidermal keratinocytes

Abstract: Epidermal expression of adhesion molecules such as desmogleins (Dsg) and cadherins is strongly affected by the differentiation status of keratinocytes. We have previously shown that certain protein kinase C (PKC) isoforms differentially alter the growth and differentiation of human epidermal HaCaT keratinocytes. In this paper, using recombinant overexpression and RNA interference, we define the specific roles of the different PKC isoenzymes in modulation of expression of adhesion molecules in HaCaT keratinocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…It has long been known that PKC signaling regulates expression of desmosomal cadherins in keratinocytes (Denning et al 1998). Suppression of PKC-a or PKC-d isoforms increases Dsg3 expression, whereas suppression of PKC-d and PKC-1 isoforms either decreases or increases Dsg1 levels, respectively (Szegedi et al 2009 (Roemer 2012) and p63 has been shown by chromatin immunoprecipitation (ChIP) to bind and activate Dsg1, Dsc3, and Dp promoters (Ferone et al 2013;Johnson et al 2014). Rho-mediated changes in the actin cytoskeleton lead to changes in Srf-dependent transcription (Miralles et al 2003) and Srf controls the expression of Pkp2 and Dsg1, which in turn drives a program of terminal differentiation (Leitner et al 2011;Dubash et al 2013), The Wnt-regulated TCF/Lef transcription complex has been implicated in regulation of Dsg4, Dsc2, Dsc3, and Pg expression but direct binding of these transcription factors to desmosomal component promoters has only been shown in a few instances (Table 1) (Bazzi et al 2009;Bailey et al 2012;Tokonzaba et al 2013).…”
Section: Transcriptional Regulation Of Desmosomal Componentsmentioning
confidence: 98%
“…It has long been known that PKC signaling regulates expression of desmosomal cadherins in keratinocytes (Denning et al 1998). Suppression of PKC-a or PKC-d isoforms increases Dsg3 expression, whereas suppression of PKC-d and PKC-1 isoforms either decreases or increases Dsg1 levels, respectively (Szegedi et al 2009 (Roemer 2012) and p63 has been shown by chromatin immunoprecipitation (ChIP) to bind and activate Dsg1, Dsc3, and Dp promoters (Ferone et al 2013;Johnson et al 2014). Rho-mediated changes in the actin cytoskeleton lead to changes in Srf-dependent transcription (Miralles et al 2003) and Srf controls the expression of Pkp2 and Dsg1, which in turn drives a program of terminal differentiation (Leitner et al 2011;Dubash et al 2013), The Wnt-regulated TCF/Lef transcription complex has been implicated in regulation of Dsg4, Dsc2, Dsc3, and Pg expression but direct binding of these transcription factors to desmosomal component promoters has only been shown in a few instances (Table 1) (Bazzi et al 2009;Bailey et al 2012;Tokonzaba et al 2013).…”
Section: Transcriptional Regulation Of Desmosomal Componentsmentioning
confidence: 98%
“…Among these, PKC␦ is present in all epidermal layers (12,20). A major role has been proposed for PKC␦ in driving keratinocyte differentiation (15,22,23,23,24,31,48). We have extensively studied the mechanism of PKC␦ regulation of differentiation using involucrin as a target (28).…”
Section: Discussionmentioning
confidence: 99%
“…Human immortalized HaCaT KCs were cultured in DMEM (Sigma-Aldrich) supplemented with 10% fetal calf serum, 2 mM L-glutamine, and antibiotics (all from Invitrogen; Bodó et al, 2005;Gö nczi et al, 2008;Kiss et al, 2008;Szegedi et al, 2009).…”
Section: Cell Culturingmentioning
confidence: 99%